Trimodal therapy and surgical approaches in stage IIIA/N2 non-small cell lung cancer - Pin-Ching Hu; Jing-Yang Huang; Ya-Fu Cheng; Ching-Yuan Cheng; Chang-Lun Huang; Wei-Heng Hung; Bing-Yen Wang (Scientific Reports)
Abstract The standard treatment guideline for stage IIIA/N2 non-small cell lung cancer (NSCLC) remains controversial despite years of research, and the necessity of surgery is still debated. This study aims to explore optimal treatment and surgical methods for stage IIIA/N2 NSCLC patients. We obtained data from the Taiwan Cancer Registry (TCR) to compare the overall survival rates of different subgroups of stage IIIA/N2 NSCLC patients, as well as the overall survival rates of different treatment strategies and surgical methods. Our study included 2,237 stage IIIA/N2 NSCLC patients. Neoadjuvant chemotherapy followed by surgery and adjuvant chemotherapy led to significantly higher survival rates. For T1N2 patients, surgery alone showed better survival (P < .001). Neoadjuvant chemotherapy with surgery and adjuvant chemotherapy provided higher survival for T2N2 and T3N2 patients (P < .001). Among surgical types, lobectomy had the lowest mortality rate, which was statistically significant. In conclusion, our study recommends neoadjuvant therapy followed by surgery and adjuvant therapy for improved survival in stage IIIA/N2 NSCLC patients. Surgery should not be excluded for resectable stage IIIA/N2 NSCLC patients, with lobectomy being the preferred option due to its significantly higher survival rate.